2017
DOI: 10.1063/1.4971627
|View full text |Cite
|
Sign up to set email alerts
|

The fracture and fragmentation behaviour of additively manufactured stainless steel 316L

Abstract: Abstract.Expanding cylinder experiments using a gas gun technique allow investigations into the ductility of metals and the fracture and fragmentation mechanisms that occur during rapid tensile failure. These experiments allow the radial strain-rate of the expansion to be varied in the range 10 2 to 10 4 s -1 . Presented here is a comparative study of the fracture and fragmentation behaviour of rapidly expanded stainless steel 316L cylinders manufactured from either a wrought bar or additive manufacturing tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Fracture strain for AISI 1018 (similar to EN3) has been reported as 46%, at strain-rates of 10 5 s -1 . In another study of stainless steel cylinders by Amott (Amott et al, 2017), failure strain was reported at ca. 25% at a strain-rate of 8.5x10 3 s -1 .…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Fracture strain for AISI 1018 (similar to EN3) has been reported as 46%, at strain-rates of 10 5 s -1 . In another study of stainless steel cylinders by Amott (Amott et al, 2017), failure strain was reported at ca. 25% at a strain-rate of 8.5x10 3 s -1 .…”
Section: Methodsmentioning
confidence: 96%
“…In subsequent work, experimental and numerical studies on expansion and fragmentation of aluminium and titanium alloy cylinders were presented (Jones et al, 2013) including initial work on the effects of the cylinder temperature (Jones et al, 2014). These and other similar studies (Amott et al, 2017;Stirk et al, 2009) demonstrated the potential of gas-gun approaches. There are other methodologies that investigate cylinder expansion including electromagnetic tube expansion studies where the cylinder exhibits deformation due to the employment of a cylindrical coil (Qiu et al, 2018) Importantly, gas-gun driven cylinder expansion and fragmentation enables greater control over strain rates compared to explosive loading (as the impact velocity of the projectile can be precisely controlled), less risk for deployment of diagnostic instrumentation and the flexibility to carry out experiments in a laboratory environment.…”
Section: Introductionmentioning
confidence: 93%